Lung Stem Cells in the Epithelium and Vasculature - Firth, Amy; Yuan, Jason X.-J (Stem Cell Biology and Regenerative Medicine,, 2015)
This book covers the identification and role of endogenous lung stem cells in health and disease, particularly the most recent advances. In addition, it discusses the rapidly growing field of stem cells and cell therapy as it relates to lung biology and disease as well as ex vivo lung bioengineering. Such approaches may provide novel therapeutic approaches for lung diseases. Human pluripotent stem cell differentiation to model the pulmonary epithelium and vasculature is also discussed. World-recognized scientists who specialize in studying both the lung epithelium and pulmonary vasculature contribute the chapters. Topics covered include: stem cell niches in the lung, the role of progenitor cells in fibrosis and asthma, iPSC in modeling lung disease, vascular repair by endothelial progenitor cells and circulating fibrocytes in pulmonary vascular remodeling. This volume of the Stem Cell Biology and Regenerative Medicine series is essential reading for researchers and clinicians interested in stem cells, lung biology and regenerative medicine. It is also an invaluable resource for advanced students studying cell biology, regenerative medicine and lung physiology.